IoT A NEW CHANCE FOR LATINAMERICA`S SMES IN COVID-19 TIMES - Romero Garibello, Julián Ricardo
Abstract   A search for models, solutions and answers have framed the economic and business history of Latin America, a region that has sailed in a sea of uncertainties of volatile indicators and little sustainability over time, now a new challenge like perhaps no other in history appears to challenge organizations, for this particular case represents more than 99% of companies in these countries, however, this situation should not necessarily be the story of an announced death, however if a new focus of opportunities that may be the potential beginning of a digital transformation and development for this area of the world. For this reason, industries 4.0, the orange economy, and digital transformation constitute a new global paradigm that does not marginalize the region, in which, of course, SMEs have a role to play in achieving the desired development of these nations in favor of general welfare of these people. This new role in technology and employment is very important, taking into account all the difficulties that are and will have to be faced by the global pandemic, therefore they will have to be highly effective in the measures that are taken, which can be dealt with. correct with the use of IoT (internet of things).   Keywords Digital Transformation, Industry 4.0, SMEs, Orange Economy, IoT.